Introducing Music to NooJ - Kocijan, Kristina (Array, 2014)
NooJ has so far been used in various analyses of textual data in a wide variety of natural languages. In this project, we intend to explore the possibility of using NooJ for the analysis of sheet music notation which can be turned into textual notation with LilyPond software. Selection of two pieces chosen from a large database of classical music available online will serve us as test corpus for this stage of our project. Description of a dictionary of terms used in sheet music notation together with the description and examples of 20 syntactic grammars used for processing sheet music are given in detail. This introduction of music to NooJ opens up the doors for different analysis such as stylistic analysis of authors, composer comparison or musical genre detection to name a few.